Measurement of the B+ → wl+[nu] branching fraction with semileptonically tagged B mesons - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We report a measurement of the branching fraction of the exclusive charmless semileptonic decay B+→ωℓ+ν, where ℓ is either an electron or a muon. We use samples of B+ mesons tagged by a reconstructed charmed semileptonic decay of the other B meson in the event. The measurement is based on a data set of 426.1 fb−1 of e+e− collisions at a center-of-mass energy of 10.58 GeV recorded with the BABAR detector at the PEP-II asymmetric-energy e+e− storage rings. We measure a branching fraction of B(B+→ωℓ+ν)=(1.35±0.21±0.11)×10−4, where the uncertainties are statistical and systematic, respectively. We also present measurements of the partial branching fractions in three bins of q2, the invariant-mass squared of the lepton-neutrino system, and we compare them to theoretical predictions of the form factors.
Im Titel ist das Pluszeichen "+" hochgestellt
Im Titel ist "Ny" (bzw. "nu") als griechischer Buchstabe dargestellt
Gesehen am 15.11.2021